ANALISA KEGAGALAN PADA PROSES TENDER SECARA PRAKUALIFIKASI METODE DUA FILE DAN EVALUASI HARGA TERENDAH - Ighfa’atuz Zuhriyah; Fitri Hardiyanti; Arie Indartono (Proceeding Maritime Business Management Conference, 2022)
Subject in this research is one of the shipbuilding companies in Surabaya which is engaged in the repair and construction of new ships. To get the project, the company participates in a tender. However, in reality, especially tenders prequalification of the two files and the evaluation of the lowest price, many failures occur. So we need a way to prevent failure in the tender. Therefore, this study aims to analyze the failure of the tender process. The method used in this research is the Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) methods. The results obtained using the FMEA method have 2 failure factors, namely the price after arithmetic correction exceeds HPS with an RPN value of 43.48 and technical personnel do not meet the requirements requested by the tender committee with an RPN value of 38,96. Meanwhile, the FTA method obtained 10 sources of causes including; poor coordination between estimators and suppliers, poor quality estimators, errors from estimators, lack of team in compiling data, not setting clear targets to be achieved, lack of understanding of competitors' weaknesses, limited manpower, few experienced workers in retirement, inadequate labor experience, and some workers who do not have competency certificates.